ANALISIS PENENTUAN HARGA POKOK PESANAN CATERING PADA CV SURYA BOGA MANDIRI DI BONTANG (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
This research aims to analysis job order cost determination which decided by CV Surya Boga Mandiri catering is higher or lower than job order cost method with full costing approach. The data analysis method used in this study is the descriptive comparative method with analysis tools that is job order costing method with full costing approach.Based on the result of this research, the cost of order according to the company amounted to Rp11.855.625. Meanwhile, according to the cost of order method with full costing approach is Rp12.919.355. There is a difference of calculation amount to Rp1.063.730. This difference lies in the charged of manufacturing overhead rates. The company imposes manufacturing overhead rates too low because the fare is not determined based on actual calculations and is considered appropriate. Furthermore there are elements of manufacturing overhead rates which are not charged by the company such as the cost of buildings, equipments and vehicles depreciation. Manufacturing overhead rates fare which is charged by the company amounted to 25% based on the company's estimate and considered to be appropriate or compatible to cover the manufacturing overhead rates on each order. While the fare of manufacturing overhead rates according to the result of the analysis is 37,84% of the total rates of raw materials on the collection of manufacturing overhead rates which actually occured. It can be concluded that the determination on cost of grilled goat orders which seted by CV Surya Boga Mandiri catering is lower than the job order cost with full costing approach.Keywords : Job order cost, full costing.